?ION EFFLUX IN COTTON ROOTS AT DIFFERENT STAGES OF DEVELOPMENT AND TEMPERATURE REGIMES - Sethar, M A; Chachar, Q A; Laidman, D L; Wilson, J M; Mirbahar, R B (Biological Sciences - PJSIR, 1998)
Cotton seeds were germinated in incubator for 48 and 60 h.The root radicles weredivided in several groups. In one group, the roots were separated into two equal halves ie, proximal and distal, in another group they were separated as long and short roots. These tissues were incubated at 35°C to analyse the electrical conductivity. In another experiment 48 and 60 h old root radicles were incubated at 30, 35 and 40°C to measure the electrical conductivity. Distal parts of roots released more electrolytes than proximal parts and short roots effluxed more electrolytes than the long roots. The 48 h old roots effluxed about double the electrolytes than 60h old roots.